Web-Based Mapping Untuk Pemetaan Lokasi Kerusakan Jalan Raya Menggunakan Cluster Marker - Agusta Praba Ristadi Pinem (ISB Atma Luhur, 2018)
Online mapping has developed rapidly over the past few years resulting to replace GIS functionality. This system allows users to use appliacation without using specialized GIS software. The system can receive data from multiple sources and display the map to all users. These developments bring web-based mapping technology. Web-based mapping using MapsAPI as third-party tools. MapsAPI allows system to mapping data in real time and real location. That information technology can support smart city program’s to solve several problem in a city like mapping the location of the damaged roads. Users only need to use internet browsing application to add location or observe the map of road damage. People and government as system user’s, can utilize the system to determine the priority of roadwork.